High throughput and low power consumption on a wireless sensor network - Bassi, Germán; Galarza, Cecilia G. (Digital signal processing, 2012)
Wireless communications are subject to fading and interferences that affect their performance. However, the broadcast nature of wireless transmissions is an advantage that has been exploited in the past to improve performance. Nodes belonging to a sensor network could listen to messages sent from other nodes and participate in this communication for the benefit of the entire network. In this paper, we present a protocol following these lines. The novelty of our approach is to obtain high throughput with low complexity and low energy consumption. ► Cooperative protocols on decentralized wireless networks are studied. ► A protocol that uses an OSTBC with unitary code rate is proposed. ► This new protocol shows an improvement in the average transmission rate. ► It also shows an overall reduction of energy consumption by the entire network. ► The cooperative protocol achieves high throughput at a reduced energy cost per bit.